Acute lymphoblastic leukaemia of the L3 subtype in adults in the Northern health region of England 1983–99. Issue 8 (1st August 2002) - Velangi, M R; Reid, M M; Bown, N; Jackson, G H; Summerfield, G P; Proctor, S J; Taylor, P R A
Abstract : Aim: Acute lymphoblastic leukaemia (ALL) with an L3 morphological FAB type is regarded by some as being synonymous with B cell ALL or ALL with a Burkitt-type chromosomal translocation—t(8;14), t(2;8), t(8;22). This paper describes a series from a population based study of 24 patients with L3 ALL presenting over 17 years. Methods: Clinical data were collected prospectively from all adult patients presenting with acute leukaemia in the Northern region since 1982. Data from all patients diagnosed with FAB type L3 ALL were analysed. Results: Overall, L3 ALL accounts for 8.6% of all adult ALL and it is more common in the elderly than has hitherto been recognised. In addition to classic Burkitt-type translocations (11 of 24 cases), the t(14;18) translocation, which is characteristically found in lower grade lymphomas such as follicular lymphoma, is frequently present (five of 24 cases). Conclusion: The presence of L3 ALL is often associated with non-Burkitt-type translocations and the presence of a t(14;18) translocation may indicate that in some cases a clinically non-apparent lymphoproliferative disorder, such as a low grade follicular lymphoma, has transformed to a more aggressive form and, thus, presents as a de novo acute leukaemia.